Digital Media Creation for Learning the Lanna Dhamma Alphabets and Writing Culture - Chinachan, Thitinadda; Fuengworatham , Amornrath; Klaynak, Konlawat (Journal of Cultural Approach, 2023)
This qualitative research focused on the study of Lanna writing culture, using the research and development (R&D) method to investigate writing culture, and design of digital media for learning the Lanna alphabet and language through online systems. The research was divided into two parts: 1) the study of documentary data on the Lanna Dhamma alphabet to create a body of knowledge; and 2) the design of digital media for promoting Lanna writing culture. The documentary research was used to design two kinds of teaching media: 1) Lanna alphabet learning media for the CMU-MOOC system, which contains a history of the Lanna Dhamma alphabets, alphabet types, numbers, the writing system, and word compounding, and 2) an online game to practice writing the Lanna alphabet and word compounding. Both created media used the same color tones: purple, black, and yellow, which are related to the main theme of the practicing game; “The Witches”. In addition, using Lanna cultural identities, as part of the designed digital media, encouraged participants to learn other dimensions of Lanna culture.